Technological Pedagogical and Content Knowledge (TPACK) in Islamic Religious Education in the Digital Era - Hidayat, Wildan Nur; Nurlaila, Nurlaila; Purnomo, Eko; Aziz, Noor (Al Hikmah: Journal of Education, 2023)
This study aims to (1) determine the supporting components and content of TPACK. (2) knowing the integration of the TPACK concept in Islamic religious education. This research method uses library (library research), data information collected by reviewing journal articles, books, and documents that are relevant to the research problem. The results of this study indicate that: (1) TPACK (Technological Pedagogical and Content Knowledge) is a combination of three components namely technology, pedagogy and some content in teaching and learning activities. (2) Integration of Islamic Religious Education (PAI) with the TPACK concept as an effort to hone and increase the skills of Islamic religious education teachers in teaching Islamic material on aqidah morals, fiqh, or the history of Islamic civilization. Among these three aspects of understanding, learning strategies emerge that are able to achieve educational goals, including developing students' creative thinking skills. TPACK in PAI starts with the teacher who must have a lesson plan (RPP).Implementation Learning) first, then applied to teaching and learning activities by integrating technology, pedagogy and educational content.